1989
DOI: 10.1029/ja094ia02p01211
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observation of atmospheric nuclear gamma radiation

Abstract: We present a satellite observation of the spectrum of gamma radiation from the Earth's atmosphere in the energy interval from 300 keV to 8.5 MeV. The data were accumulated by the gamma ray spectrometer on the Solar Maximum Mission over 3½ years, from 1980 to 1983. The excellent statistical accuracy of the data allows 20 atmospheric line features to be identified. The features are superimposed on a continuum background which is modeled using a power law with index −1.16. Many of these features contain a blend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…We have compared spectra of gamma ray lines and continua produced in the Earth's atmosphere by cosmic ray irradiation and by proton bombardment from an intense solarenergetic particle event. Our study of the quiescent spectrum from cosmic ray impact, accumulated over a 9-year period, is an incremental improvement over a detailed study performed by Letaw et al [1989] on a more limited set of data. We list the energies and widths of 20 resolved gamma ray lines observed and identify nuclei that may be responsible for the emission.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have compared spectra of gamma ray lines and continua produced in the Earth's atmosphere by cosmic ray irradiation and by proton bombardment from an intense solarenergetic particle event. Our study of the quiescent spectrum from cosmic ray impact, accumulated over a 9-year period, is an incremental improvement over a detailed study performed by Letaw et al [1989] on a more limited set of data. We list the energies and widths of 20 resolved gamma ray lines observed and identify nuclei that may be responsible for the emission.…”
Section: Discussionmentioning
confidence: 98%
“…Willett and Mahoney [1992] characterized the energies and widths of seven strong lines using the high-resolution capabilities of the germanium detectors and accumulations up to 253 days. In contrast, Letaw et al [1989] identified about 20 lines using atmospheric spectra integrated over a 3.5-year period. In this paper we describe observations of atmospheric gamma rays produced by cosmic ray interactions; these were made by the SMM spectrometer over its full 9-year lifetime.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We fitted each 3-day 'Earth minus Sun view' spectrum between 1.85-2.65 MeV by a model spectrum consisting of a power law plus three lines at 2.135, 2.310, and 2.223 MeV. As Figure 1 shows, the power law and lines at 2.135 and 2.310 MeV are the dominant features of the Earth-albedo spectrum in this energy interval (Letaw et al, 1989). Any 2.223 MeV line emission expected from the Sun ought to appear as a * A small error (-~ 5~o) was introduced into this negative solar spectrum by the small exposure to the Sun which was included in the Earth-viewing angle bins, as noted above, partially cancelling the Sun-viewing spectrum.…”
Section: Observations and Analysismentioning
confidence: 99%
“…SIMULATION The cross-sections for spallation from neutrons and protons incident on the detectors, shields and support structures were taken from Alice91 [6]. These cross-sections and the neutron and proton flux were evaluated over the [7]. This spectrum was folded through both the open collimator response and the response to shield leakage.…”
Section: Introductionmentioning
confidence: 99%